In Vivo Evaluation of the Antibacterial Activity of Sapindus rarak (Lerak) and Host Immunological Profiles in an Escherichia coli Infection Model - Lisa Savitri; Kharisul Ihsan; Elfred Rinaldo Kasimo; Rochmad Krissanjaya (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
This study evaluated the in vivo antibacterial activity of Sapindus rarak (lerak) extract and its effects on host immune responses during Escherichia coli infection. Lerak contains saponins and other bioactive compounds that have shown promising antimicrobial effects in vitro, but in vivo evidence remains limited. Male BALB/c mice were assigned to healthy, infected control, and three treatment groups receiving low, medium, or high doses of lerak extract. All infected groups were orally challenged with pathogenic E. coli and treated for seven days. Clinical signs, bacterial load, cytokines, immunoglobulin levels, and tissue histopathology were assessed. Mice in the infected control group developed weight loss, diarrhea, and systemic signs of infection, whereas those receiving lerak extract showed milder symptoms, especially at higher doses. Lerak significantly reduced bacterial counts in intestinal and systemic tissues, with the strongest effect in the high-dose group. Treatment also decreased pro-inflammatory cytokines (TNF-alpha, IL-6) and increased IL-10, indicating a shift toward controlled inflammation. Serum IgA levels were elevated in treated mice, suggesting enhanced mucosal protection. Histopathology confirmed reduced epithelial damage and inflammatory infiltration in the intestine, liver, and spleen. These findings suggest that lerak extract exerts both antibacterial and immunomodulatory effects in vivo. Its dual activity highlights its potential as a plant-derived therapeutic candidate for managing enteric infections caused by E. coli. Further fractionation and mechanistic studies are warranted to identify active compounds and clarify biological pathways involved.